PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SULAWESI SELATAN - Hehanussa, Umi Kalsum; Ruliaty, Ruliaty (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2018)
AbstractThis study aims to find out and analyze the influence of competence and motivation on the performance of employees of the Department of Manpower and Transmigration of South Sulawesi Province and to know and analyze the variables that predominantly affect the performance of employees of the Department of Manpower and Transmigration of South Sulawesi Province. The research has been conducted at the Office of Manpower and Transmiggration of South Sulawesi Province with an implementation time of 1 month, namely from January to February of 2018 with a sample of 71 people. The analysis method used in this research is quantitative descriptive method, through regression testing by conducting validity and reliability test of question items of each variable as well as assumption test. The results showed that Competency has a significant influence on performance with P = 0.021< 0.05 with a coefficient value of 0.179, this coefficient shows that the better the competence of employees, the performance of employees in the Office of Manpower and Transmigration of South Sulawesi Province will increase; Motivation has a significant influence on performance with P = 0.000< 0.05 with a coefficient value of 0.509, this coefficient shows that the better the employee's work motivation, the better the performance will be and the variable that has the dominant effect on performance is motivation, this can be seen from the beta value of 0.406 greater than other variables.